ENTREPRENEURIAL MANAGEMENT IN THE DEVELOPMENT PATTERN OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) BASED ON THE DIGITAL CREATIVE ECONOMY IN MEKARJAYA VILLAGE, SUKMAJAYA DISTRICT, DEPOK CITY: MANAJEMEN WIRAUSAHA PADA POLA PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERASIS DIGITAL EKONOMI KREATIF DI KELURAHAN MEKARJAYA, KECAMATAN SUKMAJAYA, KOTA DEPOK - Sri Yulianti; Titus Indrajaya; Mei Supriyani; Maya Sova; Septi Nur Aliva; Arif Ferdiansyah (Yayasan Education and Social Center, 2022)
This Community Service (PKM) is to educate about the science of digital-based entrepreneurial management, the creative economy of MSME actors. In the post-pandemic period, many problems are faced by the micro-scale community, especially business actors, it is still difficult to market their products and capital, seeing these problems it is necessary to have this PKM activity, with steps that entrepreneurship can take to empower business actors in the pattern of development. Creative Economy based on digital marketing. The method used is a qualitative data analysis method and a data collection tool with training and interviews. This community service is an effort to manage entrepreneurship (entrepreneurship) for micro-scale businesses based on digital creative economy. Digitization by means of independence and registration of business entities, while economic digitization can be achieved by participating in offline training, doing online marketing on digital applications, obtaining online business success tips through digital marketing media.In this community service by conducting comprehensive training and socialization to the wider community to all corners of the village or sub-district about the ease of online business for MSME Creative Economy business actors, business actors are always active in programs from both the government and the private sector to support increased income for the community. the community, especially MSME Creative Economy business actors, to immediately switch to social media or digitization consistently to optimize facilities in the pattern of creative economy development. Thus, the Social Piety Index will be realized from community entrepreneurship in the Mekarjaya Village, Sukmajaya, Depok City